Methods for Combating Unfair Competition in the Intellectual Property Market in Russia and Abroad - BYKOVA, Olga Nicolaevna; GARNOV, Andrey Petrovich; MILONOVA, Marina Valentinovna; TROKHOVA, Ekaterina Vladimirovna; PROGUNOVA, Lada Victorovna; PRIKLADOVA, Anastasiya Aleksandrovna; IVANOV, Oleg Sergeevich (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
Purpose: to reveal the characteristics of unfair competition in the intellectual property market in the Russian Federation and abroad and propose measures to combat such competition. Main results: Recommendations are presented for improving the methods for combating unfair competition in the intellectual property market. The authors propose methods which can be implemented by means of copyright protection both in the market as a whole and on the Internet, by combating trademark and service mark infringers. Besides, in order to curb unfair competition in the market, possible methods are proposed for changing the registration of domain names that allow protecting rights on the Internet. Main conclusions: In practice, there is a problem when declaring goods that contain intellectual property items). There is no registry making it possible to search for content, and search using graphic images is also difficult. In order to reduce unfair competition, it is proposed to improve the filling procedure by adding a column indicating the international registry, as well as to create a separate registry with a verbal description of images to facilitate the search. In accordance with this system, it is necessary to improve it regarding errors that are often made when filling out forms. At present, a single mistake can become a reason why the item is not selected. Solving these problems can increase control and effectiveness in terms of intellectual property protection. In most countries, unfair competition is prohibited at the legislative level. However, with the development of economic relations, the methods of unfair competition are continuously improving and becoming more and more subtle and sophisticated.